STRATIFICATION OF MODERN RUSSIAN SOCIETY: METHODOLOGY, ANALYSIS AND TREND - A. Urunov (Вестник университета)
The conducted research in modern conditions allows to allocate such classes in society as rich, average, poor and beggar. Stratification is basing on four criteria, established and justified by the author. The offered technique of social stratification includes 34 indicators, grouped in four blocks. Its transparency, clarity of reflection of vital realities in concrete indicators and availability of information on the specified criteria provide practicality of its realization in life. By results of the conducted survey of 200 experts (as of 01.01.2019), classes are represented in the following order of types and ratios: rich 7-9 %, average 20,9 %, the others – poor and beggar classes. Unfortunately, the trend of increasing reduction of the middle class in Russia and exhaustion of its potential is observed.